Interstitial deletion and ring chromosome derived from 16q. Issue 5 (May 1987) - Krauss, C M; Caldwell, D; Atkins, L
Abstract : An interstitial deletion of 16q was identified in an infant with failure to thrive, dysmorphic facies, and congenital heart defects. The mother of this infant had a similar deletion of 16q with ring formation of a fragment presumed to be derived from the deleted portion of 16q. We discuss these cases and compare them to other reports of 16q deletions.